2015
DOI: 10.21153/dlr2015vol20no2art525
|View full text |Cite
|
Sign up to set email alerts
|

Responding To Cyberbullying: The Case For Family Conferencing

Abstract:  Cyberbullying is a form of anti-social conduct which is best understood as an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…Back to the criminal justice context, Langos and Sarre (2015) explored the option of family conferences following juvenile cyberbullying. They suggested that RJ can benefit both the survivor and the responsible person (RP) in these cases.…”
Section: The Consequences Of Youth Csvmentioning
confidence: 99%
See 1 more Smart Citation
“…Back to the criminal justice context, Langos and Sarre (2015) explored the option of family conferences following juvenile cyberbullying. They suggested that RJ can benefit both the survivor and the responsible person (RP) in these cases.…”
Section: The Consequences Of Youth Csvmentioning
confidence: 99%
“…Despite these potential benefits, RJ also presents concerns in the context of youth-to youth CSO, and should not be implemented universally without specific adjustments. These concerns include the inherent power imbalance in cyberbullying (Langos & Sarre, 2015), which increases the risk of re-victimization, pressure on the survivors to participate (or not), and possible manipulation by RP, which could endanger the survivor's safety.…”
Section: The Consequences Of Youth Csvmentioning
confidence: 99%
“…On the other hand, restorative justice mechanisms vary depending on the type of online crime that was indeed committed. For instance, in cases of cyberbullying and attending to the average age of both the offender and the victim, family group conferencing seems appropriate (Duncan, 2016;Langos & Sarre, 2015), which in turn is not appropriate for online fraud, such as romantic or monetary fraud, a malware or a scareware. Thus, even though restorative justice mechanisms are seen with sympathy by cyber victims, several aspects should be taken into account in this regard.…”
Section: Restorative Justice and Cybercrimesmentioning
confidence: 99%
“…Besides these common forms, bullying may ocur in cyberspace through the use of email, texts, cell phones, Internet chatrooms, websites (Deschamps & McNutt, 2016). This new dimension of bullying is called cyberbullying, electronic bullying or online bullying (Langos & Sarre, 2015).…”
Section: Introductionmentioning
confidence: 99%